THE AESTHETIC POTENTIAL OF SACRED ART IN TRANSFORMING THE MODERN UKRAINIAN SOCIETY - Мокляк, Л. І. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2014)
The article is devoted to researching the aesthetic function of the sacredart and its place and role in the conditions of modern Ukrainian society.